Transient solid-state production of nanostructured CuS flowers - Somchai Thongtem (2018)
CuS (hcp) with different morphologies was produced using a transient solid-state reaction by the direct flow of electricity through solids, containing 1:1 molar ratio of Cu:S powders, in a high vacuum system for different lengths of time. X-ray diffraction (XRD), selected area electron diffraction (SAED), and scanning and transmission electron microscopies (SEM and TEM) specified that the products were nanostructured CuS flowers, and nanostructured CuS composing of nanoparticles with different orientations, controlled by the length of time. Raman vibrations were detected at 474.5 cm- 1, and photoluminescent (PL) emissions at 347.5 nm. Both the XRD and SAED patterns are in accordance with those obtained by the corresponding simulations. © 2009 Elsevier B.V. All rights reserved.